1995
DOI: 10.1017/s0016756800013625
|View full text |Cite
|
Sign up to set email alerts
|

Isotope studies of granitoids from the Bangenhuk Formation, Ny Friesland Caledonides, Svalbard

Abstract: The Caledonian Hecla Hoek succession in Ny Friesland, eastern Svalbard has been interpreted, for many decades, to be a continuous stratigraphic sequence. Early Palaeozoic and Neoproterozoic strata in its upper parts pass more or less conformably down into amphibolite facies rocks (Stubendorffbreen Supergroup) at depth. Recent isotopic age-determination and structural studies have indicated that the Stubendorffbreen succession is tectonostratigraphic and made up of at least three major thrust sheets. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…These terranes include significant amount of bedrock with low e Nd , <À10 in northern and northeastern Svalbard (Johansson et al, 1995(Johansson et al, , 2000(Johansson et al, , 2002(Johansson et al, , 2004Johansson and Gee, 1999). Surface sediments from a core on the Yermak Plateau north of Svalbard showed e Nd of À12.5 and it was concluded that this included material with low e Nd (À14.6) derived from Svalbard (Tü tken et al, 2002).…”
Section: The Nd In the Atlantic Inflow To The Arctic Oceanmentioning
confidence: 99%
“…These terranes include significant amount of bedrock with low e Nd , <À10 in northern and northeastern Svalbard (Johansson et al, 1995(Johansson et al, , 2000(Johansson et al, , 2002(Johansson et al, , 2004Johansson and Gee, 1999). Surface sediments from a core on the Yermak Plateau north of Svalbard showed e Nd of À12.5 and it was concluded that this included material with low e Nd (À14.6) derived from Svalbard (Tü tken et al, 2002).…”
Section: The Nd In the Atlantic Inflow To The Arctic Oceanmentioning
confidence: 99%
“…Until the 1990s the Hekla Hoek rocks, which are best exposed in the Ny Friesland block E of the AD graben and on Nordaustlandet, were regarded as an 18 km-thick synclinal basin with high-grade rocks at the bottom, grading upward to unmetamorphosed sediments and volcanic rocks (Harland, 1997;Harland et al, 1966Harland et al, , 1992. Later it was recognized that the pile contains several levels of "basement" rocks, and when radiometric dating showed these to all have similar ages (ca 1750 Ma), it became apparent that the Hekla Hoek consists of a series of stacked thrust sheets (Hellman et al, 1997(Hellman et al, , 1998Johansen et al, 1995). Gee and Teben'kov (2004) and Hellman et al (1998) have summarized the geochronological data for the Biscayerhalvøya-Holtedahlfonna Horst and its extensions further south.…”
Section: Regional and Geological Settingmentioning
confidence: 99%
“…Previous studies (Tütken et al, 2002;Maccali et al, 2013) have taken the bedrock data of granitoids from Ny Friesland in the north-east of Spitsbergen (the largest island in the Svalbard archipelago, Fig. 2, Johansson et al, 1995;Johansson and Gee, 1999) to represent the Svalbard source region. Svalbard has a wide range of rocks from different ages and in this study we characterise sediments from two catchments located in the Paleogene Central Basin, which comprises 8 % of the land area of Svalbard, and from which no prior SrNd measurements exist.…”
Section: R S Hindshaw Et Al: the Sediments Of Two High Arctic Catcmentioning
confidence: 99%